Interpretasi Konsep Pluralisme Pendidikan Islam Perspektif Nurcholish Madjid - Kholifatur Rosida Rosida; Rimanda Maulivina Maulivina; Siti Hajar Mab'ruro (Universitas Islam Negeri (UIN) Mataram, 2021)
This study takes the challenge of investigating Nurcholish Madjid's concept of pluralism related to Islamic Education. The pluralism of Islamic Education is proportional and absolute. It can produce the idea of confrontation that has been needed, and it should be customary to summarize Islamic rules with good and appropriate educational procedures and methods. Using the literature review method, the researcher then the concept of Nurcholis Madjid related to Islamic Education was asked to offer universal Education and keep all aspects of students intact. Indonesia has various kinds of differences. This requires people to interact to know one another. These differences are then able to create a variety of cultures that exist in society. One of the media that can create it is Education, as a liaison for change.